Design of Water Level Detection Using Ultrasonic Sensor Based On Fuzzy Logic - Azmi, Fadhillah; Fawwaz, Insidini; Muhathir, Muhathir; Dharshinni, N P (JITE (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING), 2019)
Water is one of the natural resources that are needed by creatures on earth. And the need for clean water is increasing, so the price of water, both bottled water and the price of water from the PDAM. Therefore, it is necessary to have a design that can control water needs, such as the water level for filling the required containers, controlling the water level in the reservoir, etc. according to human needs so that no waste of water occurs. This research was conducted to design water level detection by combining hardware and software, namely ultrasonic sensors as detection, Arduino Uno microcontroller as a process, and fuzzy logic as an analysis of data delivered by ultrasonic sensors. So, this design can be utilized in various fields both industrial and home. This water level detection is designed using ultrasonic sensors as distance monitoring, servo motor, LED warning, and buzzer. Fuzzy logic is applied to the ability of a tool designed by determining the desired set point of water. Test results that have been carried out with Fuzzy Logic with 5 levels, are level 1 (0 ? 6 cm), level 2 (6.1 ? 12 cm), level 3 (12.1 cm ? 18 cm), level 4 (18.1 cm ? 24 cm), and level 5 (24.1 ? 30 cm).